Monitoring urban heat island phenomenon in Metro Manila a remote sensing-GIS approach - Pereira, Rosalyn A. (2004)
Metro Manila , being the center of socio-economic activity in the country, attracts migrants from other regions. To accommodate the growing population, more infrastructures have been built resulting in the deterioration of the environment. Natural vegetation has been replaced by surfaces which are low-relective, non-evaporating and non-transpiring thus forming what is referred to as Urban Heat Islands (UHI). Remote sensing can detect urban growth and land surface temperature. Land use cover and surface temperature data over Metro Manila were derived over the period 1989 to 2002 using Landsat Thematic Mapper (TM) and Enhanced Thematic Mapper (ETM+) images. Supervised classification of the images using the maximum likelihood algorithm was applied to derive landcover data while surface temperature was extracted using an algorithm developed by the United States Geologic Survey (USGS). Normalized Difference Vegetation Index (NDVI)was also derived to establish the relationship between surface temperature and biophysical properties of leaf biomass. With the use of geographic information system (GIS) software, values obtained from the demographic data, landcover and surface temperature were analyzed to identify spatial pattern changes in landcover and surface temperature. UHI was modeled using a multiple linear regression equation to determine the relationship between built-up cover (BUC), population (POP), and vegetation cover (VEG), and the contribution of each of these factors to UHI. The combined use of remote sensing and GIS has been proven useful in monitoring urban growth and surface temperature which have a direct proportional relationship. An increase in surface temperature resulting from urban sprawl leads to the aggravation of UHI. Urban development has decreased vegetation cover thus decreasing surface moisture availability. Land surface temperature had an average increase of 4.5'C from 1989 to 2002 in Metro Manila. Disproportions in temperature between Metro Manila and its adjacent municipalities were also observed. In the regression analysis, no independent variable was omitted in the test for multi-colinearity. The respective correlation between the dependent and each of the independent variables was tested to affirm the inclusion of the independent variable in the multiple regression analysis. Only built-up cover (BUC) indicated strong relationship with UHI. In the regression equation, built-up cover has a contribution factor of 1.25 to UHI. The results of this study can be used by planners and decision-makers in formulating their sustainable development strategies for Metro Manila.
"October 2004."
Thesis (M.S. Remote Sensing)--University of the Philippines Diliman.
Keywords: Remote sensing -- Philippines -- Philippines -- Manila Metropolitan Area; Earth temperature -- Remote sensing -- Philippines -- Manila Metropolitan Area